Bank lending in the knowledge economy - Giovanni Dell'Ariccia; Dalida Kadyrzhanova; Camelia Minoiu; Lev Ratnovski (European Central Bank (ECB), 2020)
We study the composition of bank loan portfolios during the transition of the real sec-tor to a knowledge economy where firms increasingly use intangible capital. Exploiting heterogeneity in bank exposure to the compositional shift from tangible to intangible capital, we show that exposed banks curtail commercial lending and reallocate lending to other assets, such as mortgages. We estimate that the substantial growth in intangible capital since the mid-1980s explains around 30% of the secular decline in the share of commercial lending in banks' loan portfolios. We provide suggestive evidence that this reallocation increased the riskiness of banks' mortgage lending.
Keywords: E22; E44; G21; 330; corporate intangible capital; bank lending; commercial loans; real estate loans